Adolescent Pregnancy’s Ongoing Effects on the Depression and Anxiety Scores in Subsequent Pregnancy - Esengul Turkyilmaz; Selma Tural Hesapcioglu (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Child/adolescent 'marriages' and following pregnancies have adverse effects both on the child and adolescent mother. The aim of this study is to detect whether the adult pregnant women who have previous adolescent pregnancy more susceptible to the depression and anxiety than current adolescent pregnants and the adult pregnant women who have no adolescent pregnancy history.